Promoting Safety for Intraoperative Magnetic Resonance Imaging in the Neurosurgical Operating Room. (2nd April 2019) - Baby, Priya; Jayasuryan, Gouripriya; Muthuchellappan, Radhakrishnan; Srinivas, Dwarakanath
Abstract : Modern neurosurgery has evolved tremendously with advancing technologies and innovative modalities, such as intraoperative MRI (IOMRI). IOMRI is an operating room concept in which magnetic resonance imaging (MRI) is used during surgery to precisely understand the extent of resection of lesions. This improves surgical accuracy, thereby hugely influencing the patient outcome. This benefit, however, comes with a unique set of safety concerns. This necessitates addition of some distinctive roles for an operating room (OR) nurse. In this clinical review, we discuss the perioperative nursing concerns related to intraoperative MRI. We discuss the potential safety concerns of IOMRI and the safety precautions. We also discuss the components of the safety checklist and the role of the nurse as a safety advocate.